THE IMPLEMENTATION OF THE PRINCIPLE OF INTEGRITY IN THE LEGISLATION RELATING WITH THE PROTECTION OF ULAYAT RIGHT ON ADAT LAW COMMUNITIES - Dian Arianto (Faculty of Law, Universitas Jenderal Soedirman, 2016)
This study aims to identify and analyze the implementation of the principle of integrity in the legislation relating with the protection of ulayat rights on adat Law communities. This study used normative juridical approach. The results showed that the agrarian law as a basic reference settings related to the Natural Resources in relation to the Ulayat Rights with other regulations, particularly in Law No. 41 Year 1999, Law No. 6 Year 2014, Presidential Decree No. 71 Year 2012, and Regulation of the Ministry of Home Affairs No. 52 Year 2014 and Regulation of the Minister ATR/KBPN No. 10 Year 2016 shows the lack of synchronization substance and structure as the elaboration of the principles of integrity as mandated by the TAP MPR No.XI/MPR/2001 Keywords : the principle of integrity, ulayat rights, adat Law communities, legal protection